Development of a Thermostable Microneedle Patch for Influenza Vaccination. Issue 2 (1st December 2014) - Mistilis, Matthew J.; Bommarius, Andreas S.; Prausnitz, Mark R.
<x xml:space="preserve">Abstract</x> The goal of this study is to develop thermostable microneedle patch formulations for influenza vaccine that can be partially or completely removed from the cold chain. During vaccine drying associated with microneedle patch manufacturing, ammonium acetate and 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer salts stabilized influenza vaccine, surfactants had little effect during drying, drying temperature had weak effects on vaccine stability, and drying on polydimethylsiloxane (PDMS) led to increased stability compared with drying on stainless steel. A number of excipients, mostly polysaccharides and some amino acids, further stabilized the influenza vaccine during drying. Over longer time scales of storage, combinations of stabilizers preserved the most vaccine activity. Finally, dissolving microneedle patches formulated with arginine and calcium heptagluconate had no significant activity loss for all three strains of seasonal influenza vaccine during storage at room temperature for 6 months. We conclude that appropriately formulated microneedle patches can exhibit remarkable thermostability that could enable storage and distribution of influenza vaccine outside the cold chain. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:740–749, 2015